La trobe archaeological research in oman: The archaeology of out of africa dispersal events in oman (2019-2022) - Meredith-Williams, Matthew; Fitzpatrick, Dianne (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The debate on the timing and nature of “Out of Africa” dispersals of multiple waves of the genus Homo has been based on a limited number of securely dated sites; the majority of the Palaeolithic archaeological record for Arabia is represented by undated surface sites. This project aims to contribute to the body of knowledge and debate through targeted field survey for stratified Palaeolithic sites that can be well dated. A multidisciplinary team of geologists, geomorphologists, hydrologists, dating experts and archaeologists has been assembled to specifically target this question. Our first three survey seasons in 2019, 2020 and 2022 gave invaluable insights into the landscape setting of Oman which have fed directly into the later seasons. Preliminary results include a number of surface sites with material typologically linked to the Lower, Middle and Upper Palaeolithic of Oman, and a small number of stratified sites have been identified and are currently undergoing analysis.
Keywords: Archéologie – Oman